Changes in wealth distribution in Italy (2002-2012) and who gained from the Great Recession - Drudi, Ignazio; Tassinari, Giorgio; Alboni, Fabrizio (PSL Quarterly Review, 2017)
The aim of the paper is to analyze changes in families’ assets between 2002 and 2012; to measure changes in the degree of inequality; and to identify which social groups (or classes) have gained from these changes, using the decomposition procedure of the Gini concentration ratio proposed by Dagum (1997). The paper introduces two important methodological innovations. First, the definition of household wealth employed here is net wealth minus the value of the household’s home (if owned). Second, we develop a new method for computing the Gini coefficient in presence of negative values, and for decomposing it. JEL Classification: D10, D31